Formulasi Sediaan Hand and Body Lotion Menggunakan Ekstrak Daun Kelor (Moringa Oleifera Lam) Sebagai Antioksidan dengan Metode DPPH (1,1-Diphenyl-2-Picrylhydrazyl): Formulation Of Hand And Body Lotion Using Moringa Leaf Extract As An Antioxidant Using the DPPH (1,1-DIPHENYL-2 PICRYLHYDRAZYL) - Indriyani Indriyani; Nur Cholis Majid; Leli Nurlaeli (Jurnal Ilmiah Farmasi Indonesia (JIFIN), 2023)
Hand and body lotion is a beauty care product that is used for the body and hands to maintain moisture. Moringa leaves (Moringa Oleifera Lam) contain many free radical inhibitor molecules and several other endogenous metabolites that are rich in antioxidant activity. This study aims to determine the antioxidant activity in hand and body lotion formulations with varying concentrations of 70% ethanol extract of Moringa leaves (Moringa Oleifera Lam). The method of this research was the phytochemical testing of 70% ethanol extract of Moringa leaves (Moringa Oleifera Lam) and hand and body lotion formulations of 70% ethanol extract of Moringa leaves (Moringa Oleifera Lam) with four formulations of hand and body lotion, namely F0 (negative control) F1 (2%), F2 (3%), and F3 (4%). Furthermore, tests were carried out on hand and body lotion preparations, including organoleptic tests, homogeneity, pH, spreadability, adhesion, viscosity and antiscaldant activity tests. Based on research results, 70% ethanol extract of Moringa leaves (Moringa Oleifera Lam) contains alkaloids, tannins, saponins, and steroids. In the homogeneity test, all formulas met the homogeneity requirements. All formulas produce the same pH, which is 6, which can be said to meet the standard skin pH requirements. In the spreadability and adhesion tests, all formulas met the standard requirements of the stickiness test and spreadability test. In F2 with a concentration of 3%, the viscosity test decreased slightly, namely 1667 MS. Whereas in testing the antioxidant activity of all formulas, they are in the weak antioxidant category, namely the IC50 results are at a value of 250-500 Ppm.